Conducting successful mini-invasive laparotomy assisted artificial insemination in African Lion(Panthera leo) - Ekrami, Behrang; Nava, Hamid Ghasemzedeh; Baghbadorani, Maziar Kaveh; Nosrati, Fereshteh (BMC veterinary research, 2025)
Assisted reproductive technologies (ART), including artificial insemination (AI), represent promising tools for the conservation of genetic resources of vulnerable wild felid species. This study reports the application of AI in African lions ( Panthera leo ), using fresh semen collected via urethral catheterization under general anesthesia. Semen samples were obtained from two adult male lions and subsequently analyzed for volume, motility, concentration, and morphology. A qualified sample, measuring 0.4 mL in volume, was extended at a 1:4 ratio, using 1.6 mL of a Tris-egg yolk-based extender. Ovarian stimulation in three adult lionesses was achieved through the intramuscular administration of 1000 IU of equine chorionic gonadotropin. At 100 hours’ post-administration, behavioral and physiological indicators of estrus were observed. Subsequently, 750 IU of human chorionic gonadotropin (hCG) was administered to induce ovulation. AI was performed 36 h following hCG injection via minimal invasive midline laparotomy. A total of 0.25 mL of the extended semen, containing approximately 1 × 10⁶ spermatozoa, was deposited into each uterine horn using a 24-gauge intravenous catheter. Pregnancy diagnosis was conducted 60 days’ post-insemination using transabdominal ultrasonography. One of the three lionesses (33.3%) was confirmed pregnant, with two viable fetuses detected within the uterine horns. The pregnancy proceeded to term, lasting 115 days, and resulted in the live birth of two cubs. These findings demonstrate the feasibility and potential of minimally invasive laparotomic AI using fresh-extended semen in Panthera leo , and facilitate the utility of ART in ex situ conservation efforts for endangered felid species.